2011
DOI: 10.1007/s00425-011-1555-0
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1, a toxin produced by Fusarium verticillioides, modulates maize β-1,3-glucanase activities involved in defense response

Abstract: Fusarium verticillioides is an important pathogen in maize that causes various diseases affecting all stages of plant development worldwide. The fungal pathogen could be seed borne or survive in soil and penetrate the germinating seed. Most F. verticillioides strains produce fumonisins, which are of concern because of their toxicity to animals and possibly humans, and because they enhance virulence against seedlings of some maize genotypes. In this work, we studied the action of fumonisin B1 (FB1) on the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…They generated mutant strains in which a polyketide synthase gene ( FUM1 ) is disrupted and production of fumonisins is abrogated and found that these mutant strains were not pathogenic on maize seedlings, thus providing genetic evidence that fumonisin production by F. verticillioides is required for development of foliar disease symptoms on maize seedlings (Glenn et al, 2008). In addition, Sanchez-Rangel et al (2011) found that F. verticillioides and pure FB1 toxin suppress the activities of two basic isoforms of maize β-1,3-glucanase (PR2-like proteins). Hence they suggested that β-1,3-glucanases are relevant physiological targets of FB1 and their suppression by FB1 might contribute to F. verticillioides virulence (Sanchez-Rangel et al, 2011).…”
Section: The “Death” Connections Between Sphingolipid Metabolism and mentioning
confidence: 99%
See 1 more Smart Citation
“…They generated mutant strains in which a polyketide synthase gene ( FUM1 ) is disrupted and production of fumonisins is abrogated and found that these mutant strains were not pathogenic on maize seedlings, thus providing genetic evidence that fumonisin production by F. verticillioides is required for development of foliar disease symptoms on maize seedlings (Glenn et al, 2008). In addition, Sanchez-Rangel et al (2011) found that F. verticillioides and pure FB1 toxin suppress the activities of two basic isoforms of maize β-1,3-glucanase (PR2-like proteins). Hence they suggested that β-1,3-glucanases are relevant physiological targets of FB1 and their suppression by FB1 might contribute to F. verticillioides virulence (Sanchez-Rangel et al, 2011).…”
Section: The “Death” Connections Between Sphingolipid Metabolism and mentioning
confidence: 99%
“…In addition, Sanchez-Rangel et al (2011) found that F. verticillioides and pure FB1 toxin suppress the activities of two basic isoforms of maize β-1,3-glucanase (PR2-like proteins). Hence they suggested that β-1,3-glucanases are relevant physiological targets of FB1 and their suppression by FB1 might contribute to F. verticillioides virulence (Sanchez-Rangel et al, 2011). …”
Section: The “Death” Connections Between Sphingolipid Metabolism and mentioning
confidence: 99%
“…This study found that root hairs of Arabidopsis plants, pretreated with the PAL inhibitor, AIP, exhibited a small, but significant, suppression in levels of AL-PCD induced by SA or FB1, whereas gibberellic acid/abiotic stress induced death levels remained unchanged. Moreover, the rise in sphinganine levels caused by FB1 temporarily coincided with the induction of PAL transcript in maize [66] and the sphingolipid elicitor was also shown to induce mitogen activated protein kinase, which was required for PAL gene induction [67]. Therefore this data suggests that the PAL pathway does contribute to signalling involved in the induction of PCD by SA or FB1 in Arabidopsis root hairs.…”
Section: Discussionmentioning
confidence: 70%
“…Fusarium verticillioides, causal agent of kernel and ear rot diseases of maize, produces polyketides including fumonisins [32]. While the role of fumonisins in plant pathogenesis is less clear, they are known to impact beta-1,3-glucanases involved in plant defense [33]. Fumonisins have also been identified by chemical means in closely related Sordariomycetes insect pathogens [34] and species of Aspergillus (Eurotiomycetes) [35].…”
Section: Plant Pathogensmentioning
confidence: 98%